Ensino em sustentabilidade na formação do Engenheiro Agrônomo: um estudo de caso - Alves, Jessica Mieko Ota (2019)
Brazil in the 21st century is marked by a scenario that encompasses diverse social vulnerabilities, political instability, individual fragmentation, among other drawbacks. However, it is also possible to find environmental aspects that conflict with the needs of economic growth, especially in the agricultural area Due to the fact that the Agronomist deals with issues that directly involve nature and society, and because they are unbalanced at the present time, the process of university education becomes relevant in the context of initiatives with potential to overcome problems, which oppress the population and the environment. Thus, sustainability reveals itself as a strategy of transformation of the current paradigm and education is a vehicle capable of operationalizing it. In this sense, the present case study aimed to analyze how the concept of sustainability is is presented in the pedagogical proposal of the undergraduate degree in Agronomy of the Federal University of Uberlândia in the Uberlândia campus, as well as to verify how the theme is being apprehended by the egress students, to diagnose what is the meaning of sustainable development that propagates in that intellectual environment. To this end, the methodology used was qualitative, descriptive approach, through interview based on guiding topic, participant observation, content analysis and documentary analysis, in which were examined: the curriculum, the disciplinary records and the data that characterize the educational institution referred to as sustainable. The evaluation period was from May 2019 to August of the same year. The results show that the entity develops educational and organizational actions aimed at promoting sustainability within its internal public policies, including the dissemination of programming in its own mass media. The research also showed that the pedagogical project of the undergraduate degree in Agronomy of the Federal University of Uberlândia contemplates the intention to effect the citizen formation through the inclusion of the sustainability in the daily of the academic activities, while the curriculum and the disciplines forms offer a reasonable amount of disciplines and materials directed to the discussion of the subject, however, these instruments are disconnected between them, each dealing only with what belongs to it. Regarding the actual situation detected, the perception of sustainability in the course by the students is mediocre, there is a poor use of the sustainability content in the professional and personal lives of the individuals who graduate there and the involvement of the community. Sustainability projects are still insignificant, indicating the dissociation between theory and practice. Therefore, it is concluded that student learning in sustainability suffers little impact from interventions promoted by higher education. Therefore, as a technological product resulting from this research, it is suggested to generate a checklist for diagnosis and readjustment of the strategic orientation of the course in relation to sustainability and changes in the curriculum, so that the training can really fulfill what it promises.